Clinical instructors' recruitment callenges: Interpretive Structural Modeling approach - Akram Sadeghian; Shahram Tofighi; Nikoo Yamani; Tahereh Changiz (Wolters Kluwer Medknow Publications, 2020)
CONTEXT: Universities of medical sciences are responsible for educating and training human resources (HRs) that provide services to all members of the community. Clinical educators play a significant role in the promotion of health and education in medical sciences universities. AIMS: The aim of this study was to prioritize and develop a model to illustrate the relationship between faculty recruitment challenges in medical sciences universities. SETTINGS AND DESIGN: Interpretive structural modeling (ISM) is a system design method initially introduced by Warfield (1974). This method helps create order in the complex interconnections between components of a system by interpreting the opinions of a group of experts. It both determines the priority of elements influencing one another and uncovers the association between the elements of a multipart set in a hierarchical structure. SUBJECTS AND METHODS: In this method, the identified challenges were built into a paired comparison questionnaire to be completed by policymakers and experts. By the same token, the obtained results were analyzed with the ISM technique. STATISTICAL ANALYSIS: The four steps include identified variables related to the issue, structural self-interaction matrix, initial reachability matrix, and final reachability matrix was used for analysis. According to these steps, the ISM model was portrayed. RESULTS: The ISM model was developed in ten levels that divided into three parts including key challenges, strategic challenges, and dependent challenges. CONCLUSION: Health promotion and quality of education in medical sciences universities is dependent on quality of faculty recruitment system. According to the results, it is imperative that HR managers and policymakers improve existing rules and develop policies to solve the challenges in this area.